Improving Import Food Safety. - Ellefson, Wayne (Institute of Food Technologists Series., 2012)
Improving Import Food Safety presents detailed information on solutions for addressing the safety of imported foods and ingredients. It provides a valuable reference for food companies and food professionals from industry, government, and academia, the book presents a thorough understanding of the issues and difficulties involved. Offering factual information from both U.S. and international perspectives, expert authors highlight issues, processes used by industry in the U.S. and other countries, and processes to be used going forward. Through numerous case studies, Improving Import Food Safet.